EFFECT OF POSTPARTUM PERIOD ON SUPEROVULATORY RESPONSE IN CROSSBRED AND INDIGENOUS CATTLE - PATEL, D V; BHALODIA, S D; CHAUDHARI, N N; PATIL, S R; BHATOL, J G; SHRMA, H C; DEVANAND, C P (The Indian Journal of Animal Reproduction, 2023)
Large numbers of factors are responsible for the superovulatory response in bovines and one of them is calving to flushing interval. Milking animals are under considerable stress due to negative energy balance postcalving which considerably affects the reproductive system. Sizeable number of crossbred and indigenous donor cows were superovulated and flushed at different stages post-calving, i.e. <90 days, 90-150 days, 150-300 days and >300 days. The pooled mean total embryos recovered were 7.57, 7.29, 7.98 and 4.31 , respectively. The corresponding mean viable embryos recovered were 2.64, 4.90, 4.69 and 3.88, respectively for the four postpartum periods. Although there was no significant difference with respect to total embryo recovery, there was non-significantly less number of viable embryo recovery in < 90 days group compared to all other groups. Superovulatory response with recovery of total and viable embryos per donor was better at all intervals postpartum in crossbreds as compared to indigenous cows. In both, crossbred and indigenous animals, the viable embryo recovery rate was low compared to the total embryo recovery rates when the donors were flushed before 90 days post-calving.